ANALISIS INTERVENSI KUALITAS LABA DALAM HUBUNGAN KINERJA KEUANGAN DAN NILAI PERUSAHAAN DI NEGARA BERKEMBANG - Devi, Ni Luh Nyoman Sherina; Ida Ayu Ratih Manuari (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2025)
This research aimed to examine the role of earnings quality in mediating the relationship between financial performance and firm value in emerging markets. The research employed a sample of 85 manufacturing firms listed on the Indonesia Stock Exchange during 2021-2023 period and utilized the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Financial performance was measured using return on assets, current ratio, debt to equity ratio, and total asset turnover; firm value was proxied by price earnings ratio, price to book value, and Tobin’s Q; and earnings quality was proxied by the Earnings Response Coefficient (ERC). The findings indicated that financial performance had a significant positive effect on firm value but did not significantly influence earnings quality. Furthermore, earnings quality had no significant effect on firm value, neither mediate the link between financial performance and firm value. These findings suggest that investors in Indonesia’s capital market still prioritize traditional financial metrics rather than earnings quality.